Autologous Bone Augmentation in Combination with an Ameloblastoma in the Maxillary Region- A Case Report? - Vasilios, Alevizakos; Marcus, Stoetzer; Constantin, von See (Archives of Clinical and Medical Case Reports, 2018)
Maxillary ameloblastomas are rare odontogenic tumours. This case report describes a patient who presented with an ameloblastoma in the maxillary molar region. In this case, bone surrounding tooth 28 was removed together with the tooth itself and the cystic mass to perform an augmentation at 11 for subsequent implant placement. Histological examination of the mass revealed it to be an ameloblastoma. This called for an extensive follow-up resection at tooth 28 and removal of the augmentation material at 11.